Social Resilience Through Play Therapy: Towards a Transformative Social Practice - Garšvė, Lina; Povilaitienė, Neringa; Sukažauskaitė, Viktorija (Socialinė teorija, empirija, politika ir praktika, 2025)
In social work, play therapy is applied as a sociocultural service for organizing children’s employment, but also as a social action that transforms social reality. Play therapy is aimed at getting to know the child, identifying children’s problems, and enabling the child to develop social skills and resistance to negative social influence through participation in the construction of social reality. According to research data, children feel happier, more relaxed, and surrounded by better emotions while playing, but, at the same time, a reality is constructed that allows us to move from a ‘culture of silence’ to a ‘culture of voice’. Therefore, play therapy is applied in order to raise children’s emotional well-being, to recognize the lack of social skills, contributing to children’s better self-esteem, self-confidence and more successful critical involvement of children in the social reality around them.After studying the context of application of the play therapy method as a sociocultural service, while recognizing the lack of social skills of clients, it became clear that play therapy helps to recognize the lack of social skills. The results of the study showed that day center visitors often lack communication and conflict resolution skills. The lack of these abilities robs individuals of the tools they can use critically to develop resilience against the dominant or surrounding social environment. The application of game therapy promotes the reflection of the participants about their social situation and promotes the reflection of social reality through the processes of participation in it.
Keywords: play therapy; social action; social resilience; day care center